La « région métropolitaine trinationale du Rhin supérieur » : contrer la périphérie étatique par la centralité métropolitaine - Pauline Pupier (Belgeo)
In 2010, the cross-border cooperation between Germany, Switzerland and France became the “trinational metropolitan region of the Upper Rhine”. This article aims at drawing the genesis of this new strategy. It relies on a geographic and scalar approach and uses data from a document analysis and a corpus of interviews. It points out that German regional actors were the true drivers of the strategy. They reacted to the federal agenda on metropolitanisation and created a cross-border consensus aligned with the German political and academic standards. In fact, the metropolitan argumentation raised European awareness and forced the national recognition of a trinational metropolitan region. The actors of the Upper Rhine use the centrality component of metropolitanisation in order to counteract the peripheral component of state border. This case study presents a process of cross-border region building which includes a national and a supranational re-scaling process.